2013
DOI: 10.1128/aac.01348-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotic Use on Carbapenem Resistance in Pseudomonas aeruginosa: Is There a Role for Antibiotic Diversity?

Abstract: fIn this study, we aimed to evaluate the relationship between the rates of resistance of Pseudomonas aeruginosa to carbapenems and the levels and diversity of antibiotic consumption. Data were retrospectively collected from 20 acute care hospitals across 3 regions of Switzerland between 2006 and 2010. The main outcome of the present study was the rate of resistance to carbapenems among P. aeruginosa. Putative predictors included the total antibiotic consumption and carbapenem consumption in defined daily doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…In the same period, increasing trends of consumption were observed for tigecycline and colistin. 19 However, the evidence is lacking that decrease in utilization is followed by recovery of susceptibility to antibiotics. We observed that the reduction in utilization of carbapenems and piperacillin/tazobactam was associated with a decrease in resistance density of P. aeruginosa isolates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same period, increasing trends of consumption were observed for tigecycline and colistin. 19 However, the evidence is lacking that decrease in utilization is followed by recovery of susceptibility to antibiotics. We observed that the reduction in utilization of carbapenems and piperacillin/tazobactam was associated with a decrease in resistance density of P. aeruginosa isolates.…”
Section: Methodsmentioning
confidence: 99%
“…Also Previous studies showed that there was positive correlation between increase in utilization of carbapenems and resistance of P. aeruginosa to these antibiotics. 19 However, the evidence is lacking that decrease in utilization is followed by recovery of susceptibility to antibiotics. Our study showed that during a relatively short period of 5 years a decrease in utilization of carbapenems and piperacillin/tazobactam was associated with decreased density of resistant P. aeruginosa isolates ( Figure 1A,B).…”
Section: Data On Annual Antimicrobial Consumption (Oral and Parenteral)mentioning
confidence: 99%
“…Arguably, heterogeneity in the ecological sense is better captured using the concept of diversity, as introduced in the following section. In order to provide compatibility with the terminology based on the notion of "heterogeneity" suggested in relevant publications on antibiotics resistance [10,8], we cannot completely drop this term.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…In other words, R a is a monotonous function of D a , thus, the two measures can be used interchangeably without loss of information since diversity has only a 1 Please note that the typesettings of the formulas for HI in refs. [10,8] are incorrect. relative meaning, anyway.…”
Section: Heterogeneity and Entropymentioning
confidence: 99%
See 1 more Smart Citation